The geography of creative industries in Europe: Comparing France, Great Britain, Italy and Spain - Rafael Boix Domenech; Luciana Lazzeretti; Francesco Capone; Lisa De Propris; Daniel Sanchez (European Regional Science Association (ERSA), 2010)
The creative economy is a holistic and multidisciplinary concept that deals with the interaction between economics, culture and technology, and centred on the production of creative contents in goods and services. One of the most relevant dimensions of creativity is the territorial one. Despite the emphasis put on the theoretical definition of creativity, the measurement of creative industries and the use of these concepts in macro units as well as in isolated case studies, it is necessary to strengthen comparative research for the identification and analysis of the kind of creativity embedded in the territory, its determinants and its patterns of concentration. This compared research relies on the measurement of the creative industries and the identification of their territorial patterns of distribution in the local production systems of five European countries: Italy, France, the United Kingdom, Spain and Portugal. Creative local production systems are identified in these countries departing from local labour markets as territorial units, firms and jobs in creative industries, and focusing on two different kinds of creative industries: traditional cultural industries and technology-related creative industries. The results show that creative industries are more important in some countries like Italy and the United Kingdom, and that their spatial patterns of distribution are significantly different across countries, where three basic models emerge: distributed, concentrated and polarized. The implications of these patterns on the analysis of creative industries as well as on the design and implementation of policies are discussed.
Keywords: L22; R12; L82; 330; creative industries; local creative systems; spatial concentration